Impact of social institutions on developmentof сhild's genius - Galina Lemko; Bogdan Kovbas (Vasyl Stefanyk Precarpathian National University, 2017)
In the article the types of gift are distinguished and influence is grounded on development of gift of child of such social institutes as seed, preschool establishments, school and out-of-school educationally-educator establishments. Key words: gift, child, family preschool establishments, general educational establishments, out-of-school educationally-educator establishments.